Potensi Interaksi Obat Antihiperlipidemia Pada Pasien Stroke Iskemik Rawat Inap Di RS X Kabupaten Indragiri Hilir Tahun 2022 - Nursyifa; Armini Hadriyati; Yuliandani (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2025)
Abstract: Ischemic stroke is caused by a blockage or blood clot that occurs in the brain. Stroke has various risk factors and complications that cause patients to receive many medications (polypharmacy). Polypharmacy can increase the potential for drug interactions that can harm patients. One of the treatment options for ischemic stroke is antihyperlipidemic therapy. Antihyperlipidemia statin group is the first choice of treatment of hyperlipidemia. The purpose of this study was to determine the types of antihyperlipidemic drugs, types of comorbidities, types of mechanisms and severity in stroke patients receiving antihyperlipidemic therapy at X Hospital, Indragiri Hilir Regency in 2022. Data were collected retrospectively in the form of 57 medical records of ischemic stroke patients with therapy inpatient antihyperlipidemia. Data analysis was carried out descriptively. Based on the results of the study it was concluded that the potential for drug interactions occurred in 87 (26.69%) cases that experienced interactions and 239 cases (73.31%) did not experience drug interactions. Based on the type of interaction, there were 84 pharmacokinetic interactions (96.55%) and pharmacodynamic mechanisms in 3 cases (3.45%). Based on the strength of the interaction, major interactions were found in 15 (17.24%) cases, moderate severity in 71 (81.61%) cases, and minor severity in 1 (1.15%) cases. Based on the interacting drugs, there were 3 most, namely atorvastatin with amlodipine 27 cases (31,03%), atorvastatin with clopidogrel 16 cases (18,40%), and simvastatin with amlodipine 15 cases (17,24%). For the statistical analysis of the chi square test, there was a significant relationship between severity and the number of drugs p=0.004, severity and age p=0.003, and there was no significant relationship between severity and comorbidities p=0.236. Keywords: Antihyperlipidemia, Drug Interactions, Ischemic Stroke